Engineering of Saposin C Protein Chimeras for Enhanced Cytotoxicity and Optimized Liposome Binding Capability - Suzanne I. Sandin; David M. Gravano; Christopher J. Randolph; Meenakshi Sharma; Eva de Alba (MDPI AG, 2021)
Saposin C (sapC) is a lysosomal, peripheral-membrane protein displaying liposome fusogenic capabilities. Proteoliposomes of sapC and phosphatidylserine have been shown to be toxic for cancer cells and are currently on clinical trial to treat glioblastoma. As proof-of-concept, we show two strategies to enhance the applications of sapC proteoliposomes: (1) Engineering chimeras composed of sapC to modulate proteoliposome function; (2) Engineering sapC to modify its lipid binding capabilities. In the chimera design, sapC is linked to a cell death-inducing peptide: the BH3 domain of the Bcl-2 protein PUMA. We show by solution NMR and dynamic light scattering that the chimera is functional at the molecular level by fusing liposomes and by interacting with prosurvival Bcl-xL, which is PUMA's known mechanism to induce cell death. Furthermore, sapC-PUMA proteoliposomes enhance cytotoxicity in glioblastoma cells compared to sapC. Finally, the sapC domain of the chimera has been engineered to optimize liposome binding at pH close to physiological values as protein-lipid interactions are favored at acidic pH in the native protein. Altogether, our results indicate that the properties of sapC proteoliposomes can be modified by engineering the protein surface and by the addition of small peptides as fusion constructs.